Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.3945/jn.112.166835
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteinemia in Mice with Genetic Betaine HomocysteineS -Methyltransferase Deficiency Is Independent of Dietary Folate Intake

Abstract: Elevated homocysteine (Hcy) concentrations are associated with increased risk of several chronic diseases. Hcy can be removed by methylating it to form methionine via either the betaine homocysteine S-methyltransferase (BHMT) or the methionine synthase (MS) pathway. BHMT uses betaine as the methyl donor, whereas MS uses 5-methyltetrahydrofolate. We previously found that mice with the gene encoding Bhmt deleted (Bhmt(-/-)) had altered Hcy metabolites in tissues. This study aimed to determine whether folate supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 12 publications
2
22
0
Order By: Relevance
“…Young (2–3‐mo‐old) C57BL/6J Bhmt −/− mice showed increased concentrations of plasma homocysteine compared with their wild‐type littermates, confirming previous reports (49) ( Fig. ).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Young (2–3‐mo‐old) C57BL/6J Bhmt −/− mice showed increased concentrations of plasma homocysteine compared with their wild‐type littermates, confirming previous reports (49) ( Fig. ).…”
Section: Resultssupporting
confidence: 90%
“…Bhmt showed the highest cochlear expression of the methionine metabolism genes studied; furthermore, its expression in connexin 30–knockout mice has been related to stria vascularis permeability and hearing loss (8). In our hands and as reported, Bhmt −/− mice showed hyperhomocysteinemia and reduced hepatic methylation index (30, 49). However, no evident signs of hearing loss were observed at the ages studied compared with wild‐type mice.…”
Section: Discussionsupporting
confidence: 88%
“…Indeed, several studies have demonstrated a positive effect of methyl-group donor supplementation on correcting 1-carbon metabolism perturbations (48,49); however, when these disturbances were caused by an impairment of the remethylation homocysteine to methionine and conversion of homocysteine to glutathione in the transsulfuration pathway, methyl donor supplementation was not effective. For example, it has been reported that the SAH-homocysteine disturbances caused by Bhmt-or Cbs-deficiency are independent of dietary methyl donor supplementation (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…The results suggest that folate enhanced SAM production via the methionine synthase pathway, but was not able to remove tHcy in this mouse model. The BHMT pathway appears to substantially participate in tHcy metabolism in mice [50]. At least in this mouse model, folic acid supplementation did not counterbalance the metabolic burden caused by disrupting the BHMT enzyme.…”
Section: Metabolic Burden Of a Methyl-deficient Dietmentioning
confidence: 99%